(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study examined the impact of economic hardship on the implementation of economic programmes in secondary schools in Nigeria. The study concluded that economic hardship has effect on the entire system of economics programme implementation in secondary schools. Teachers face low morale and limited professional development opportunities; students struggle with access and concentration due to financial stress; and schools lack the instructional materials necessary for effective teaching. Based on these findings, the study recommends that the government should allocate more financial resources to the education sector, particularly for the implementation of economic programmes in secondary schools. Adequate funding will ensure the provision of modern instructional materials, training for economics teachers, and the maintenance of school infrastructure. To enhance the productivity and motivation of economics teachers, government and school authorities should improve teachers’ welfare through timely salary payments, incentives, and professional development programmes. Regular workshops, seminars, and refresher courses should be organized to update teachers on modern economic trends and innovative teaching methods. This will help improve their instructional effectiveness despite the prevailing economic challenges. Schools should explore low-cost and digital instructional resources to enhance teaching and learning of economics.